Integrative analysis of Ewing’s sarcoma reveals that the MIF-CD74 axis is a target for immunotherapy - Fangzhou He; Jiuhui Xu; Fanwei Zeng; Boyang Wang; Yi Yang; Jie Xu; Xin Sun; Tingting Ren; Xiaodong Tang (Cell Communication and Signaling)
Abstract Background Ewing’s sarcoma (EwS), a common pediatric bone cancer, is associated with poor survival due to a lack of therapeutic targets for immunotherapy or targeted therapy. Therefore, more effective treatment options are urgently needed. Methods Since novel immunotherapies may address this need, we performed an integrative analysis involving single-cell RNA sequencing, cell function experiments, and humanized models to dissect the immunoregulatory interactions in EwS and identify strategies for optimizing immunotherapeutic efficacy. Results EwS is infiltrated by immunosuppressive myeloid populations, T and B lymphocytes, and natural killer cells. We found that SLC40A1 and C1QA macrophages were associated with a poor prognosis, whereas CD8+ T-cell infiltration was associated with a good prognosis. A comparative analysis of paired samples revealed that in tumors with a good chemotherapeutic response, macrophages presented increased antigen presentation and reduced release of protumor cytokines, whereas CD8+ T cells presented increased cytotoxicity and reduced exhaustion. An interaction analysis revealed a vast immunoregulatory network and identified MIF-CD74 as a crucial immunoregulatory target that can simultaneously promote M2 polarization of macrophages and inhibit CD8+ T-cell infiltration. Importantly, MIF blockade effectively reshaped the tumor immune microenvironment, turning cold tumors hot and inhibiting tumor growth. Conclusions Our integrative analysis revealed that the MIF/CD74 axis is a promising target for the treatment of Ewing sarcoma and provides a rationale for this novel immunotherapy.